Analysis of Proteins and Piwi-Interacting RNA Cargo of Extracellular Vesicles (EVs) Isolated from Human Nose Organoids and Nasopharyngeal Secretions of Children with RSV Infections - Tiziana Corsello; Nicholas Dillman; Yingxin Zhao; Teodora Ivanciuc; Tianshuang Liu; Antonella Casola; Roberto P. Garofalo (Viruses, 2025)
Respiratory syncytial virus (RSV) is the leading cause of respiratory infections in children. Extracellular vesicles (EVs), released by airway epithelial cells, contain proteins and different families of non-coding RNAs (EV cargo) that can modulate the responses of target cells to viral infection. Nasal mucosa is a primary site of viral entry and the source of EVs present in the upper airway secretions. In this study we characterized proteins, including inflammatory mediators and cytokines, and the piwi-interacting RNA (piRNAs) cargo of EVs isolated from pediatric human nose organoids (HNO) and nasopharyngeal secretions (NPS) positive for RSV. Using Proximity Extension Assay (PEA) and Luminex multi-target arrays, we found significant enrichment in several chemokines and other mediators/biomarkers, including CCL2, CCL20, CXCL5, CX3CL1, CXCL6, MMP-1, MMP-10, uPA, Flt3L, ARNT and CD40 in EVs secreted by RSV-infected HNO compared to control mock HNO. Analysis of NPS samples from RSV infected children revealed that CCL3, CCL20, CXCL8, uPA, VEGFA, were concentrated in the NPS-EV fraction. LC-MS/MS and Gene Ontology indicated that RSV positive NPS-EVs originate from different cellular sources, with the most abundant proteins from neutrophils and epithelial cells. A total of 490 piRNAs were detected by NGS sequencing of small RNA libraries obtained from NPS-EVs, which has not been reported prior to this study. Identification of inflammatory mediators and small non-coding RNAs which are compartmentalized in EVs contributes to understanding mechanisms of virus-mediated pathogenesis in RSV infections.